Management of adverse effects of topical PDT. (1st April 2019) - Ibbotson, S.H.; Wong, T.H.; Morton, C.A.; Collier, N.J.; Haylett, A.; McKenna, K.E.; Mallipeddi, R.; Moseley, H.; Rhodes, L.E.; Seukeran, D.C.; Ward, K.A.; Mohd Mustapa, M.F.; et al.
Summary: Photodynamic therapy (PDT) is commonly used to treat certain types of low risk non‐melanoma skin cancer and pre‐cancerous sun damage and is available in many dermatology services. The purpose of this review was to examine the published evidence in the medical literature about side effects of this form of treatment and approaches to preventing and treating these side effects. This was part of a larger process to review and update the guidelines for use of PDT and its place in dermatology practices, which is published separately in the British Journal of Dermatology (Wong et al., Br J Dermatol 2018 https://doi.org/10.1111/bjd.16838 ). The current article reviewed all published evidence concerning the side effects of PDT and also put this into context based on the wide experience of the authors who are actively involved in the undertaking of PDT in the dermatology clinic. The authors found that discomfort and pain during PDT treatment were the only main side effects of note but that these could be reduced considerably by using modified low intensity treatment protocols, and that usually this therefore did not limit treatment or its outcomes. Rare side effects included becoming allergic to the drugs used in PDT and this was most likely if patients had multiple treatments to large areas. There were no other notable side effects and it was overall concluded that treatment was well tolerated and that PDT was important to have available in dermatology practices. This reinforces the role and importance of PDT as a safe and effective treatment option for certain skin conditions, in particular thin non‐melanoma skin cancers and pre‐cancerous sun damage